(untitled) (Research, Society and Development, 2024)
Ankyloglossia is a congenital condition characterized by the presence of a fold of tissue that limits the movement of the tongue, which can affect functions such as speech, eating and oral hygiene. Its early diagnosis is essential to ensure adequate speech and eating development, preventing future complications and promoting a better quality of life. Thus, the present study aimed to discuss the importance of the Tongue Test in identifying ankyloglossia and its relevance for early intervention. To this end, a narrative review of the literature was carried out in the Scholar Academic and VHL (Virtual Health Library) article bases, through the crossing of keywords: ankyloglossia, diagnosis, treatment and nutrition. Inclusion criteria: epidemiological studies in general, literature reviews, published in the last 10 years in Portuguese or English and available for download. Relevant Brazilian laws, decrees, technical notes and resolutions were also included. The exclusion criteria were laboratory studies, dissertations and theses, letters to the editor and conference abstracts. After the selection and analysis stages, 18 articles were considered for this literature review. The Tongue Test is a simple and efficient exam that allows for the early identification of ankyloglossia while still in the maternity ward. The present study showed that the Tongue Test is a crucial tool for the early identification of ankyloglossia. This practice, together with appropriate interventions, can significantly mitigate the negative impacts of the condition on the baby’s health, including nutrition, promoting more natural and uncomplicated development.